EVALUASI KEMURNIAN GENETIK DENGAN MARKA MIKROSATELIT DAN APLIKASI RIZOBAKTERIA UNTUK MENINGKATKAN PRODUKSI DAN MUTU BENIH JAGUNG HIBRIDA - Memen Surahman; . Giyanto; Andi Takdir; Awaludin Hipi (Jurnal Ilmu Pertanian Indonesia, 2012)
One effort to improve of high-quality of maize seed were the development and application of methods for genetic quality testing, such as SSR marker. Another effort was used of rhizobacteria for increased the availability of nutrients, especially P in the soil. The aim of this study were: 1) Microsatellite markers specific to male and female parents of maize hybrid; 2) Seed genetic purity by using molecular marker; 3) Rhizobacteria that could increase the physiological quality of maize hybrid seed; and 4) Rhizobacteria that could increase the growth of plant and efficiency of fertilizer P. The result showed that: 1) From five markers tested, three markers namely phi96100, phi328175 and phi072 produced polymorphic bands and capable to distinguish parental lines of two maize hybrids. Microsatellite marker phi96100 was specific used for testing genetic purity of cv.Bima-4 and phi072 for cv.Bima-3. While phi328175 was specific markers to both hybrids maize. The test of cv. Bima-3 and Bima-4 indicated that genetic purity of both varieties were 97.5% and 80% respectivelly; 2) Isolates B28 and B46 could increase IV 19% and 22% respectively, and had a high speed of growth compared controls; 3). Isolates B46, B42, B13, P14, P31, AB2, AB3, AB11, ATS4, and ATS5 could increased of germination compared to control; 4) Treatment of rhizobacteri significantly affects on plant height 2, 4 and 6 week after planting (WAP); 5) P fertilizer dosage were not significantly influenced on the number of leaves at 2 and 4 WAP, but significant at 6 WAP. Isolate of B28, B42 and ATS4 were potential for increased of plant growth.